GENDER CONSTRUCTION IN CHILDREN'S EDUCATION: AN ANALYSIS OF EQUAL ACCESS AND TREATMENT IN EDUCATIONAL INSTITUTIONS - Nenny Kurniaty Lisfa; Kahar, M. Iksan; Ramlah Dahlan; Nadya Humairah Ramadhany (Musawa: Journal for Gender Studies, 2025)
Gender construction in early childhood education plays a crucial role in shaping children’s identities, attitudes, and future social roles. Educational institutions are not only spaces for knowledge transmission but also arenas where gender norms and values are socially reproduced. This study aims to analyze how gender construction influences equality of access and treatment for children within educational institutions. The research focuses on identifying gender biases embedded in curricula, teaching practices, learning materials, and institutional policies that affect children’s educational experiences. This study employs a qualitative library research method with a descriptive-narrative design. Data were collected from national accredited journals (SINTA) and international journals indexed by Scopus published within the last five years. The data were analyzed through content analysis, critical interpretation, and comparative synthesis of relevant theories and empirical findings. The results indicate that gender inequality in early childhood education often occurs implicitly through stereotypical roles, differential teacher expectations, and unequal participation opportunities. These practices contribute to the reinforcement of gender-based limitations on children’s cognitive, emotional, and social development. The study highlights the importance of integrating gender-responsive approaches in curriculum development, teacher training, and educational policy. This research contributes theoretically by strengthening social construction and critical pedagogy perspectives and practically by providing recommendations for creating inclusive, equitable, and child-friendly educational environments.